Nitrogen fertilization rate and method influences water and nitrogen productivity of forage winter wheat. (31st December 2020) - Lenssen, Andrew W.; Sainju, Upendra M.; Jones, Clain; McVay, Kent; Angvick, Terry
Abstract: Spring‐seeded annual forages are well adapted to the Great Plains; however, the influence of application rate and method of N fertilization on winter wheat (WW) ( Triticum aestivum L.) forage productivity is unknown. A field study was conducted in a factorial design for 3 yr to determine the influence of N application rate and method on water and N productivity of awnletted WW 'Willow Creek'. Urea was either broadcast or banded at planting using N fertilization rates of 0, 28, 56, and 84 kg N ha −1 . The N application rate × method interaction was significant only for WW height. Weed herbage was low at WW forage harvest, 19 kg ha −1 . As N fertilization rate increased from 0 to 84 kg N ha −1, wheat stem density and height increased by 70 and 78%, respectively, and herbage increased by 58%. Increased N rate increased WW water use quadratically, but water productivity (kg biomass ha −1  mm −1 ) was 68% greater at 84 kg N ha −1 . However, N application method did not influence water use or productivity. Banded N application increased N accumulation in WW herbage by 11% compared to broadcast N. Increasing N rate reduced N productivity by 24% compared to 0 kg N ha −1 . Willow Creek WW produced greater herbage yield as N fertilization rate increased with banded application. Willow Creek is a highly productive fall‐planted forage in this predominantly spring‐planted small grain–grain legume region. Core Ideas: Response of forage winter wheat to the N rate and method is unknown. Greater available N increased stem height, stem density, and herbage yield. Water productivity of forage winter wheat increased with increased available N. Banded N fertilization at planting improved N recovery index compared to broadcast N fertilization. Forage yield was maximized at 16.9 kg available N Mg −1  forage.